Evaluation of Heavy Metal Levels and Water Quality Index of Al-Diwaniyah River - Dhafer Hameed Majeed Al Taie,; Monia EL Bour, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The growing global concern for heavy metal contamination highlights its significant threat to both human health and the environment. The Al-Diwaniyah River, a crucial freshwater source for a large population in Iraq, has been increasingly polluted due to rapid urbanization and industrial activities over recent decades. Compounding the issue, the unstable economic situation in Iraq has led to inadequate monitoring of the river's water quality in many critical areas. This study aimed to address this gap by conducting a thorough analysis of heavy metal concentrations (Pb, Cd, Zn, Fe, Cu) and the overall water quality of the Al-Diwaniyah River. Four strategically selected sampling sites were chosen based on their proximity to agricultural, urban, and industrial activities along the riverbank. Samples of both water and sediment were collected during summer 2023 and winter 2024. Heavy metal concentrations were determined using atomic absorption spectroscopy, while physical and chemical properties were assessed using a water analysis kit. The results reveal a higher concentration of heavy metals during the summer months compared to winter, with site 4, located near rubber and textile factories, showing the highest levels of contamination. Conversely, site 1 had the lowest heavy metal concentration. The water quality index (WQI) mirrored these findings, with site 4 exhibiting the poorest water quality (WQI of 767-1374), and site 2 showing better quality (WQI of 343-494). The overall WQI for the river was found to be 840 in summer and 384 in winter, indicating that the river is heavily polluted. Consequently, the water from the Al-Diwaniyah River is unsuitable for drinking without extensive treatment.